KEMANDIRIAN USIA DINI DI SUKU BAJO - HEWI, LA (Program Studi Magister Pendidikan Anak Usia Dini, 2015)
Abstract: This study aims to: (1) Describe the forms of independence, (2) Describe the parenting parents establish the independence, (3) Describe the attachment of children with parents establish the independence, (4) Describe the role of teachers in shaping the independence. Analysis of the data used that model of Miles and Huberman. The research data obtained from observation, interviews and documentation. Results of the study include: (1) There is a child who has not seen an independent behavior, child behavior only seen one self-contained and there are children who have seen all mandirinya behavior, (2) Parents with permissive parenting tend to have children who are not independent and the parents with authoritative parenting tend to have an independent child, (3) Stickiness children with mothers in different schools with home, (4) Teachers make efforts to foster self-confidence of children and train children to be responsible. Keywords: independent, parenting, attachment, children, teachers